Oenothera L. a new genus of alien plant first reported in the Maltese Islands - Tavilla, Gianmarco; Lanfranco, Sandro (Phytotaxa, 2025)
The genus Oenothera is extensively naturalized across Europe, owing to its high reproductive capacity, adaptability, and efficient seed dispersal mechanisms. This study reports the first documented occurrence of Oenothera rosea in the Maltese Islands, as well as the first record of the genus Oenothera in the territory. This finding represents a significant addition to the local flora and marks a new record of alien plants. A morphological description of O. rosea and information on its distribution, ecological characteristics, and identification key are provided. The discovery of O. rosea underscores the growing trend of biological invasions in Malta, driven primarily by human activities and mass tourism. Its occurrence in anthropized areas indicates potential for further spread into agricultural landscapes and other human-altered environments, raising concerns about its ecological impact.